Edukasi Kesehatan Tentang Hipertensi Dalam Meningkatkan Pengetahuan Lansia Dan Mengelola Tekanan Darah Tinggi - Kurniati Mayasari,WD; Centia Komalasari; Afridon; Armanda Trimurti; Putri Nona Sari; Fauri Irvani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The elderly are a group that is vulnerable to complications due to hypertension, such as stroke, heart failure, chronic kidney disease, and even sudden death. Hypertension or high blood pressure is one of the most common non-communicable diseases found in society and is a major cause of morbidity and mortality worldwide. The World Health Organization (WHO) states that approximately 1.28 billion people worldwide suffer from hypertension, with most cases undiagnosed and not receiving adequate treatment. Hypertension counseling for the elderly aims to provide education about the causes, impacts, prevention, and treatment of high blood pressure through an easy-to-understand approach. In addition, this activity is also expected to encourage the elderly to adopt a healthy lifestyle, such as reducing salt consumption, doing light physical activity, and complying with recommended medical therapy. The activity was carried out for the elderly with a total of 17 participants at the KTK Community Health Center Polyclinic, Solok City. Lectures and question and answer discussions were used to develop knowledge about complications, hypertension factors, symptoms and signs, prevention and treatment, etc. The media used were slides and leaflets. The tools used to carry out this activity are: leaflets and a list of questions related to the extension material which will be distributed before and after the extension.